2020
DOI: 10.1111/cns.13444
|View full text |Cite
|
Sign up to set email alerts
|

DHA modulates MANF and TREM2 abundance, enhances neurogenesis, reduces infarct size, and improves neurological function after experimental ischemic stroke

Abstract: Aims: Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a secretory neurotrophic factor protein that promotes repair after neuronal injury. The microglia cell surface receptor (triggering receptor expressed on myeloid cells-2; TREM2) regulates the production of pro-and antiinflammatory mediators after stroke. Here, we study MANF and TREM2 expression after middle cerebral artery occlusion (MCAo) and explore if docosahexaenoic acid (DHA) treatment exerts a potentiating effect. Methods: We used 2 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…In intracerebral hemorrhage, TREM2 activation attenuates neuroinflammation and neuronal apoptosis by activating PI3K/Akt 96 . Taken together, microglial TREM2 may play a neuroprotective role in stroke and is a promising therapeutic target for the treatment of acute brain injuries 97,98 …”
Section: Microglia/macrophage Phagocytosis Signaling In Response To C...mentioning
confidence: 99%
“…In intracerebral hemorrhage, TREM2 activation attenuates neuroinflammation and neuronal apoptosis by activating PI3K/Akt 96 . Taken together, microglial TREM2 may play a neuroprotective role in stroke and is a promising therapeutic target for the treatment of acute brain injuries 97,98 …”
Section: Microglia/macrophage Phagocytosis Signaling In Response To C...mentioning
confidence: 99%
“…Numerous epidemiological studies and large-scale clinical trials have shown that the neuroprotective effects of dietary fatty acids after stroke may be related to their anti-inflammatory properties. 128 However, recent data also show that bioactive dietary fatty acids, such polyunsaturated fatty acids (PUFAs) or saturated fatty acids (SFAs), can cross the BBB to regulate microglia function, including phagocytosis. [124][125][126] Several in vitro studies in other CNS diseases have assessed the effect of PUFAs of the n-3 series on microglia phagocytosis and found that docosahexaenoic acid (DHA, 22:6n-3) and eicosapentaenoic acid (EPA, 20:5n-3) increased peptide ingestion by microglia in AD 129 and up-regulated gene expression of biomarkers associated with phagocytosis under myelin pathology.…”
Section: Dietary Therapy Targeting Microglia Phagocytosis For Stroke ...mentioning
confidence: 99%
“…Minor MANF expression was also found in astrocytes of the ischemic cortex but not in the normal healthy brain ( Shen et al, 2012 ). In a more recent study, Belayev et al found that docosahexaenoic acid increased MANF protein expression in neurons and astrocytes of the peri-ischemic region 24 h after transient MCAo in rats ( Belayev et al, 2020 ). Yang et al showed increased MANF expression in microglia/macrophages at the same time point after transient MCAo, and a further increase in MANF positive microglia/macrophages was seen when animals with stroke were pretreated with bone marrow mesenchymal stem cells ( Yang et al, 2020 ).…”
Section: Manf and Xbp1 In Strokementioning
confidence: 99%
“…However, in the rat dMCAo model, the RTDL sequence is not needed for neuroprotection, implying that KDEL receptors do not have a significant role in mediating MANF’s neuroprotective effect on cerebral ischemia ( Matlik et al, 2015 ). Taking a different approach, Belayev et al used docosahexaenoic acid (DHA) to increase endogenous MANF protein expression after transient MCAo and observed neuroprotection and enhanced neurogenesis associated with DHA therapy ( Belayev et al, 2020 ). An important study on 18- to 20-month-old mice was conducted recently by Han et al and showed that the recombinant MANF protein given 2 h post-MCAo is also neuroprotective in the aging brain ( Han et al, 2021 ).…”
Section: Manf and Xbp1 In Strokementioning
confidence: 99%
See 1 more Smart Citation